Identification of candidate biomarker MRPL23 and its prognostic potential in non-small cell lung cancer with emphasis on the squamous cell carcinoma subtype - Podemska, Edyta; Gostomczyk, Karol; Jerka, Dominika; Borowczak, Jędrzej; Gagat, Maciej; Grzanka, Dariusz; Durślewicz, Justyna (Frontiers in Oncology, 2026)
IntroductionLung cancer remains the leading cause of cancer-related mortality worldwide, with non-small cell lung cancer (NSCLC) accounting for the majority of cases. Despite advances in therapy, survival remains poor due to late diagnosis and treatment resistance. Identification of reliable prognostic biomarkers is essential to improve risk stratification and clinical outcomes.MethodsMRPL23 expression was evaluated as a potential prognostic biomarker in NSCLC using immunohistochemical analysis of tumor specimens from 110 patients and mRNA expression data from The Cancer Genome Atlas (TCGA) cohort. Associations between MRPL23 expression and clinicopathological features, as well as overall survival, were analyzed using survival statistics.ResultsMRPL23 expression was significantly higher in NSCLC tissues than in normal lung tissues (p < 0.0001), with particularly elevated levels observed in squamous cell carcinoma. High MRPL23 protein expression was detected in 57 of 110 cases (51.8%) and was associated with shorter overall survival (median OS 34 vs. 48 months; HR 1.62, 95% CI 1.01–2.58, p = 0.04). These findings were validated in the TCGA cohort, where high MRPL23 mRNA expression correlated with worse overall survival (HR 1.46, 95% CI 1.17–1.83, p < 0.01).DiscussionMRPL23 overexpression, particularly in lung squamous cell carcinoma, is associated with poor prognosis and may serve as an independent prognostic factor in NSCLC. These results suggest that MRPL23 represents a promising biomarker for improving risk stratification and guiding personalized therapeutic strategies in patients with NSCLC.